Entwicklung miniaturisierter Aktorsysteme basierend auf magnetischen Formgedächtnislegierungen - Pinneker, Viktor (Schriften des Instituts für Mikrostrukturtechnik am Karlsruher Institut für Technologie / Hrsg.: Institut für Mikrostrukturtechnik, 2019)
In this work, the actuation principles of single-crystal Ni-Mn-Ga alloys based on the magnetic shape memory effect (MSM-effect) and the coupling between their magnetic, mechanical and thermal properties, are investigated. The MSM effect is generated by the magnetically induced reorientation of the crystal structure. Thereby, the magnetic strain up to 10 % can be reached.